Relaxation of yeast mitochondrial functions after whole-genome duplication - Jiang, Huifeng; Guan, Wenjun; Pinney, David; Wang, Wen; Gu, Zhenglong (Genome Research, 2008)
Mitochondria are essential for cellular energy production in most eukaryotic organisms. However, when glucose is abundant, yeast species that underwent whole-genome duplication (WGD) mostly conduct fermentation even under aerobic conditions, and most can survive without a functional mitochondrial genome. In this study, we show that the rate of evolution for the nuclear-encoded mitochondrial genes was greater in post-WGD species than pre-WGD species. Furthermore, codon usage bias was relaxed for these genes in post-WGD yeast species. The codon usage pattern and the distribution of a particular transcription regulatory element suggest that the change to an efficient aerobic fermentation lifestyle in this lineage might have emerged after WGD between the divergence of Kluyveromyces polysporus and Saccharomyces castellii from their common ancestor. This new energy production strategy could have led to the relaxation of mitochondrial function in the relevant yeast species.
10.1101/gr.074674.107